Diagnosis of external invasive cervical tooth resorption and its management using biodentine - Harakh Chand Branawal; Jyoti Yadav; Prachi Rani; Silviya Samad; Aiyman Ayubi (Wolters Kluwer -Medknow Publications, 2022)
Invasive cervical resorption (ICR) is a rare advancing and expansionist kind of external tooth resorption that commences within the cervical region. The treatment goal must be a complete elimination of all resorbing tissues and restoration of the resorptive defect with the placement of an acceptable filling material to achieve desired function and esthetics. The successful outcome of treatment depends on early detection and proper diagnosis. This article shows the detection and management of maxillary right central incisor in a 24-year-old female diagnosed with ICR, using biodentine and resin-modified glass ionomer cement.